Variable-length-to-variable length source coding: a greedy step-by-step algorithm - Fabris, F. (IEEE transactions on information theory, 1992)
Some results on variable-length-to-variable-length source coding are presented. A sufficient criterion for the asymptotic optimality of the generic V-V code is given. This also allows the study of the Tunstall-Huffman scheme performance. Then, a nonoptimal greedy approach to prefix codes is described, based on the informational divergence pseudometric and on the Gallager algorithm minimization of the current rate, associated with the subsequent extensions of the source probability distribution. Although optimality is not always reached, this technique can be usefully employed to improve the Tunstall-Huffman concatenation.< >